2016
DOI: 10.1002/jts.22091
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mental or Physical Health Problems in a Combat Zone: Comparisons of Postdeployment Mental Health and Early Separation From Service

Abstract: The primary aim of this study was to evaluate whether being treated for mental health or nonbattle physical injury during military combat deployment was associated with higher risk for postdeployment mental disorders and poorer career outcomes than seen in the general combat-deployed population. Service members treated in theater for mental health (n = 964) or noncombat injury (n = 853) were compared with randomly sampled personnel (n = 7,220) from the general deployed population on diagnosed mental disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Similarly, within the Australian Navy, the onset of a psychiatric disorder during military service was related to a 19% greater risk of separation overall, and the majority of those leaving military service did so within the first year after symptom onset (Creamer et al, 2006). Finally, a recent study examined deployed Army, Navy and Marine Corps service members over a 3-year period, comparing rates of early separation across (a) members treated for mental disorders and (b) treated for noncombat physical injuries, and (c) a random sample of deployed personnel (Conway et al, 2016). Rates of early separation for medical and punitive reasons in the first group were twice as high as the second group and three to five times as high as the third group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, within the Australian Navy, the onset of a psychiatric disorder during military service was related to a 19% greater risk of separation overall, and the majority of those leaving military service did so within the first year after symptom onset (Creamer et al, 2006). Finally, a recent study examined deployed Army, Navy and Marine Corps service members over a 3-year period, comparing rates of early separation across (a) members treated for mental disorders and (b) treated for noncombat physical injuries, and (c) a random sample of deployed personnel (Conway et al, 2016). Rates of early separation for medical and punitive reasons in the first group were twice as high as the second group and three to five times as high as the third group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a review of U.S. Army and Marine Corps post-deployment health assessment data indicated that, within a year after deployment, individuals who met criteria for a psychiatric disorder were significantly more likely than individuals who did not meet criteria to separate from military service for any reason [ 24 ]. More recently, a study examining rates of early separation among deployed Army, Navy, and Marine Corps SMs found that rates of early separation for individuals treated for mental disorders were twice as high as those treated for non-combat physical injuries, and three to five times higher than a random sample [ 16 ]. Although separation includes voluntary as well as involuntary reasons, the current study findings replicate these earlier studies that have identified earlier career separations for those with mental health concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions such as substance use disorders and severe personality disorders that limit one’s ability to interact effectively within the unit toward mission completion may lead SMs to be considered “not suitable for duty” and they may be referred for an administrative separation from service [ 13 , 14 ]. Further, studies have found that pre-deployment mental health problems and post-deployment conditions such as PTSD may be associated with misconduct that can ultimately lead to punitive discharge [ 15 , 16 ]. Notably, these conditions have relatively low base rates and make up only a small fraction of a percent of those seeking mental health care, suggesting the impact these “known” cases have on stigma is extremely disproportionate.…”
Section: Introductionmentioning
confidence: 99%